High performance work practices and their associations with health, happiness and relational well-being: are there any tradeoffs? - Guerci, Marco; Hauff, Sven; Gilardi, Silvia (International journal of human resource management, 2022)
Employee well-being is a multidimensional construct, hence high performance work practices (HPWPs) may have diverse effects on its various dimensions. However, extant research does not provide any compelling conclusion regarding the possibility of such tradeoff effects since researchers have usually focused on single well-being dimensions while using diverse research designs (e.g. samples from different countries, different conceptualizations and measures of HPWPs and employee well-being). Diversely, this paper explores the relationship between employees' perception of HPWPs and three well-being dimensions (health, happiness, and relational well-being) using a probabilistic sample (n = 1,364 employees), from a single country (i.e. Germany), and a set of uniform measures of HPWPs and employee well-being. The findings show that some HPWPs indeed present tradeoff effects on different dimensions of employee well-being. Therefore, we argue that it is necessary to adopt an analytic view on the relationships between HPWPs and employee well-being.